Mechanical and durability properties of epoxy mortar incorporating coal bottom ash as filler - Lakhiar M.T.; Bai Y.; Wong L.S.; Paul S.C.; Anggraini V.; Kong S.Y. (Elsevier Ltd, 2023)
Ash handling; Ashes; Cements; Coal; Coal ash; Epoxy resins; Fillers; Mortar; Particle size; Shrinkage; Silica fume; Water absorption; Coal bottom ash; Different proportions; Epoxy; Epoxy mortar; Experimental investigations; Ground coal bottom ash; Mechanical and durability properties; Micro-fillers; Particles sizes; Property; Fly ash